Eksplorasi Psikologis: Studi Kasus Terhadap Muncikari Gigolo - Ambarwati, Tri; Fakhri, Nurfitriany; Nurdin, Muhammad Nurhidayat (LPPM Universitas 17 Agustus 1945 Samarinda, 2024)
In the prostitution business, procurers are intermediaries between clients and prostitutes, both male and female. Procurers are tasked with handling conflicts and incentives in their work. The aim of this research is to understand the psychological dynamics of a respondent regarding their motivation to become a procurer and the impact of this profession on them. This research is a qualitative research study with a case study approach. The main respondent in the study was one woman accompanied by one other person as a significant other. In this research, data were collected using semi-structured interviews. The results of data analysis show that the respondent's decision to become a procurer was influenced by a toxic relationship environment, traumatic events, financial difficulties, and family separation. The respondent experienced several negative impacts on their psychological condition, even though they felt safe about their financial condition. These negative impacts were losing concern for others, hurting themselves, feeling guilty about what they did, and giving in to pressure. The psychological insights gained from this study have significant implications for mental health practitioners working with individuals involved in prostitution, while contributing to the broader academic discourse on psychological adaptation in such complex social environments.